Observational study on quality of life, safety, and effectiveness of first‐line cetuximab plus chemotherapy in KRAS wild‐type metastatic colorectal cancer patients: the ObservEr Study. (17th October 2016) - Pinto, Carmine; Di Fabio, Francesca; Rosati, Gerardo; Lolli, Ivan R.; Ruggeri, Enzo M.; Ciuffreda, Libero; Ferrari, Daris; Lo Re, Giovanni; Rosti, Giovanni; Tralongo, Paolo; Ferrara, Raimondo; Alabiso, Oscar; et al.
Abstract: Cetuximab improves efficacy when added to chemotherapy for metastatic colorectal cancer (mCRC). Effective management of skin reactions from cetuximab improves quality of life (QoL), and treatment compliance in clinical trials. No data are available from real‐world settings. The ObservEr observational, multicenter, prospective study evaluated QoL, the incidence of skin reactions, and management of chemotherapy plus cetuximab in first‐line for mCRC. The primary endpoint was QoL measured with the Dermatology Life Quality Index (DLQI) and EORTC QLQ‐C30. Secondary endpoints were the incidence of skin and serious adverse events, median overall and progression‐free survival, tumor response, and resection rates. Between May 2011 and November 2012, 228 patients with KRASwt mCRC were enrolled at 28 Italian centers, 225 evaluable, median age 65 years. QoL did not change during treatment and was not affected by the choice of prophylactic or reactive skin management. The incidence of cetuximab‐specific grade ≥3 skin reactions was 14%, with no grade 4/5 events. Skin reactions correlated with survival ( P  = 0.016), and their incidence was influenced by chemotherapy regimen (oxaliplatin vs. irinotecan—Incidence rate ratio [IRR] 1.72, P  < 0.0001) and gender (male vs. female—IRR 1.38, P  = 0.0008). Compliance at first postbaseline evaluation was 97.75%. Median overall survival was 23.6 months, median progression‐free survival 8.3 months. Cetuximab plus chemotherapy did not compromise QoL in the routine clinical setting when patients receive close monitoring plus prophylactic or reactive management of skin reactions. We observed the same correlation between overall survival (OS) and skin reactions reported in controlled clinical trials, also in this setting. Abstract : Cetuximab improves efficacy when added to chemotherapy for metastatic colorectal cancer (mCRC). Cetuximab plus chemotherapy did not compromise QoL in the routine clinical setting when patients receive close monitoring plus prophylactic or reactive management of skin reactions.